1993
DOI: 10.1038/bjc.1993.458
|View full text |Cite|
|
Sign up to set email alerts
|

Genistein modulates the decreased drug accumulation in non-P-glycoprotein mediated multidrug resistant tumour cells

Abstract: In tumour cells the pharmacological basis for multidrug resistance (MDR) often appears to be a reduced cellular cytostatic drug accumulation caused by the drug efflux protein, P-glycoprotein (Pgp MDR), or by other drug transporters (non-Pgp MDR). Here we report the reversal of the decreased daunorubicin (DNR) accumulation in five non-Pgp MDR cell lines (GLC4/ADR, SW-1573/2R120, HT1080/DR4, MCF7/Mitox and HL60/ADR) by genistein. Genistein inhibited the enhanced DNR efflux in the GLC4/ADR cells. In these cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
90
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 31 publications
4
90
1
Order By: Relevance
“…Moreover, unlike PGPresistant cell lines, it has been shown that in LRP, as well as MRP over-expressed cell lines, cyclosporine A, or cyclosporine derivatives including SDZ PSC 833 (PSC), could not restore drug accumulation (Kuiper et al, 1990;Barrand et al, 1993). On the other hand, it has been shown that some other drugs, such as verapamil, amiodarone or genistein, had a moderate activity (Kuiper et al, 1990;Barrand et al, 1993;Versantvoort et al, 1993;Cole et al, 1994;Van der Graaf et al, 1994). The aim of our work was to study PGP, LRP and MRP expression in leukaemic blast cells, and to investigate their relationship with the cells' ability in accumulating DNR, or in retaining Rhodamine 123, in the presence or absence of the MDR reversal agent SDZ PSC 833.…”
mentioning
confidence: 99%
“…Moreover, unlike PGPresistant cell lines, it has been shown that in LRP, as well as MRP over-expressed cell lines, cyclosporine A, or cyclosporine derivatives including SDZ PSC 833 (PSC), could not restore drug accumulation (Kuiper et al, 1990;Barrand et al, 1993). On the other hand, it has been shown that some other drugs, such as verapamil, amiodarone or genistein, had a moderate activity (Kuiper et al, 1990;Barrand et al, 1993;Versantvoort et al, 1993;Cole et al, 1994;Van der Graaf et al, 1994). The aim of our work was to study PGP, LRP and MRP expression in leukaemic blast cells, and to investigate their relationship with the cells' ability in accumulating DNR, or in retaining Rhodamine 123, in the presence or absence of the MDR reversal agent SDZ PSC 833.…”
mentioning
confidence: 99%
“…contrast to MRP mediated MDR, is readily reversed by drugs such as verapamil, cyclosporin A and the cyclosporin analogue PSC833 [9]. A potent specific inhibitor of MRP mediated daunorubicin (DNR) transport is the isoflavonoid genistein [9].…”
Section: Introductionmentioning
confidence: 99%
“…11,18 Expression of drug resistance proteins Expression of drug resistance proteins was measured using an optimized method for childhood ALL cells as recently described. 19 The expression of P-gp was detected by MRK16 (mouse IgG2a, 5 g/ml; Kamiya Biomedical Company, Thousand Oaks CA, USA).…”
Section: Dnr Accumulation and Retentionmentioning
confidence: 99%
“…These data confirm earlier reports by others and validate the presently applied method. 11,18 The effects of the modulators on the accumulation and retention of DNR in childhood ALL cells was only small in the majority of cases. As shown in Figure 3, the median change in accumulated DNR content after 60 min of uptake was +2.5% for 2 M PSC 833 (range −5% to +24%; n = 42), +2% for 4 M CsA (range −9% to +22%; n = 25), +11.5% for 6 M Vp (range −17% to +95%; n = 14) and −2.5% for 25 M genistein (range −10% to +10%; n = 10) compared with the accumulated DNR content in the absence of modulators.…”
Section: Modulating Effect On Dnr Accumulation and Retentionmentioning
confidence: 99%
See 1 more Smart Citation